Metode Muqaran dalam Penafsiran Al Quran - Ananda, Dea Putri; Eliyani, Eliyani; Ramadhani, Lutfia Eka; Sukti, Surya (UNIVERSITAS SERAMBI MEKKAH, 2025)
The source of Islamic teachings is based on the Qur'an As-Sunnah and hadith as its foundation pillars, where the Qur'an is the holy book of Muslims and As-Sunnah is all the actions of the prophet and hadith all the prophet's sayings which are recorded, which is the area of ​​study of Al- The Qur'an covers the 16th, 17th centuries up to present civilization. Different periods and scholars interpret from century to century with various models of interpretation carried out by scholars such as character research models, thematic research models, ancient manuscript research models (philology), living Qur'an research models, and comparative research models as well as criticism given to literal (literalistic) interpretations to know the direct meaning of the verses of the Qur'an.